Slovak Shakespeare in American Exile - Marcinčin Matúš (Slovenské divadlo)
Ján Vilikovský’s synthesizing monograph Shakespeare u nás (2014) is a great study; however, it does not include the whole history of translations of Shakespeare’s dramas into the Slovak language. Slovak literary and theatre studies have not reflected this theme in relation to Slovak cultural exile after the year 1945. In the present contribution, the author completes the mentioned monograph by Vilikovský, he adds and deals especially with translations written in exile by Andrej Žarnov and Karol Strmeň. He pays special attention to the fragments of translations of Shakespeare’s dramas found as a manuscript in the inheritance left after the tragic death of their author Karol Strmeň. The author reconstructs the fragments and then analyses and compares them with relevant Slovak and Czech translations of Shakespeare’s works. As a result of this study, it can be concluded that the translations by Strmeň written in a modern, cultivated, although slightly archaic Slovak language would have achieved an important position in the history of Slovak translations of Shakespeare’s drama if they had been published.